2018
DOI: 10.1021/acs.jpcc.8b08417
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Coinage-Metal···Fullerene Adducts. Evaluation of the Interaction Nature between Triangular Coinage Metal Complexes (M3 = Cu, Ag, and Au) and C60 through Relativistic Density Functional Theory Calculations

Abstract: The recent formation of [M 3 (3, ) 2 Pz) 3 ]−C 60 cocrystals in a 4:1 ratio have shown the coinage metal complex's ability to bind fullerene, acting as buckycatchers. Here, we clarify the nature of such interaction accounting for the stabilization of the whole assembly via two models of different 4:1 and 1:1 ratios, within the framework of relativistic dispersion-corrected density functional theory. Our results exhibit a strong van der Waals character in the interaction, supported by the electrostatic characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 68 publications
(113 reference statements)
0
11
0
Order By: Relevance
“…Metalloporphyrins have many roles in a variety of fields including chemical, medical, biologic, and physic. The Interaction of porphyrin and ligand or metalloporphyrin with other compounds can be observed by Density Functional Theory (DFT) calculation approach [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Metalloporphyrins have many roles in a variety of fields including chemical, medical, biologic, and physic. The Interaction of porphyrin and ligand or metalloporphyrin with other compounds can be observed by Density Functional Theory (DFT) calculation approach [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…We also investigated the nature of the interactions in N 2 O and CO adducts of C 59− n BN n , which seems to be affected by the composition of fullerene. 74,75 The quantum theory of atoms in molecules (QTAIM) 76 was used here to investigate the nature of interactions between fullerenes and adsorbed N 2 O or CO molecules. QTAIM is based on topological analysis of electron density, which determines the nature of a chemical bond by analyzing electron density at a specific point between interacting atoms, known as the bond critical point (BCP).…”
Section: Theoretical Detailsmentioning
confidence: 99%
“…[36] The terms regium bond (RgB) and coinage bond (CiB) have been used indistinctly in the literature to describe noncovalent interactions involving elements belonging group 11 (Cu, Ag and Au). [37,38] Both theoretical and experimental studies have been reported [39][40][41][42][43][44][45][46] that illustrate the ability of group 11 of elements to participate in σ-hole interactions. In addition, the interplay between RgBs and other noncovalent interactions has been also analyzed theoretically.…”
Section: Introductionmentioning
confidence: 99%